Novel Adhesive Nanocarriers Based on Mussel-Inspired Polyglycerols for the Application onto Mucosal Tissues - Keerthana Rajes; Peer Nölte; Cynthia V. Yapto; Kerstin Danker; Henrik Dommisch; Rainer Haag (MDPI AG, 2022)
A synthetic route for adhesive core-multishell (CMS) nanocarriers for application to the oral mucosa was established using mussel-inspired catechol moieties. The three CMS nanocarriers with 8%, 13%, and 20% catechol functionalization were evaluated for loading capacity using Nile red, showing an overall loading of 1 wt%. The ability of Nile red loaded and functionalized nanocarriers to bind to a moist mucosal surface was tested in two complementary adhesion assays under static and dynamic conditions using monolayers of differentiated gingival keratinocytes. Adhesion properties of functionalized nanocarriers were compared to the adhesion of the non-functionalized nanocarrier. In both assays, the CMS nanocarrier functionalized with 8% catechol exhibited the strongest adhesion compared to its catechol-free counterpart and the CMS nanocarriers functionalized with 13% and 20% catechol.